The effect of lubrication in reducing net friction in warm powder compaction process - Nor S.S.M.; Rahman M.M.; Tarlochan F.; Shahida B.; Ariffin A.K. (2023)
Warm powder compaction process is an advanced type of the conventional cold compaction process in producing a green compact, which is conducted at elevated temperature. Metal powder inside a die is compressed completely after heating the whole system at elevated temperature ranges from 100 C to 150 C. During the compaction process, friction occurs between the metal powder, the die surface and between the powders itself. The entire compaction phases as well as the density of green compact are eventually affected because of the process. The aim of this paper is to discuss the effect of lubrication in term of the mixing time, weight percent of lubricant and the density of metal powder through warm compaction. The metal powder that used was in the process was an iron ASC 100.29. The compaction experiments have been conducted at 130 C and the lubricants used was zinc stearate and carbon. It was found that the compaction phases (compaction and ejection) are strongly dependant on the variables used. 2007 Elsevier B.V. All rights reserved.